PD-L1 Expression in Muscle-Invasive Urinary Bladder Urothelial Carcinoma According to Basal/Squamous-Like Phenotype - Kim, Bohyun; Lee, Cheol; Kim, Young A.; Moon, Kyung Chul (Frontiers in Oncology, 2020)
Urothelial carcinoma (UC) is the most common histologic type of urinary bladder cancer and muscle-invasive UC shows aggressive behaviors. Programmed cell death-1 (PD-1) /programmed cell death ligand 1 (PD-L1) blockades have been approved as standard treatments for patients with advanced stage UC. A total of 166 muscle-invasive urinary bladder cancer (MIBC) patients, who underwent transurethral resection of the bladder or cystectomy from 2004 to 2010 were included. We evaluated PD-L1 expression by the SP142 and SP263 assays, and classified the cases “positive” or “negative” according to the manufacturer’s recommendations. We performed immunohistochemistry (IHC) for cytokeratin (CK) 5/6, CK14, GATA3, FOXA1, and CK20 and classified samples as Basal-Squamous-like (BASQ) or non-BASQ subtype. The overall concordance rate for PD-L1 expression 91.6%. (152/166) (kappa =0.732). The SP142 assay showed 15.1% positivity, the SP263 assay showed 23.5%. The high positivity in the SP142 and SP263 assay were significantly correlated with positive CK5/6, CK14 expression, negative GATA3, FOXA1 and CK20 expression. Classification according to IHC expression resulted in 12.0% (20/166) of samples being classified as BASQ subtype and 88.0% (146/166) of samples being classified as non-BASQ subtype. High positivity in the SP142 and SP263 assay was significantly correlated with the BASQ subtype (p<0.001, both). Our study is the first to analyze the association of immunohistochemically defined BASQ and non-BASQ subtypes with two PD-L1 assays in MIBC. In conclusion, we revealed that a high PD-L1 positive rate in all PD-L1 assays was significantly associated with the BASQ-subtype, and these results suggests that the BASQ classification may be important to apply the PD-1/PD-L1 blockades in MIBC.